HOW TO USE DIFFERENTIATED INSTRUCTION - Nazarova A.T. (World Scientific Reports, 2023)
This article discusses the use of differentiated learning in education. Differentiated learning is designed to meet the individual needs of a larger number of students. This is not only an important process for improving classroom efficiency, but also the only way to ensure fair education for different students. I want to personalize student learning, improve their learning ability, develop students' ability to manage learning, and enable them to learn and grow throughout their lives.